Atomic-scale study of the {112¯1} twinning and {112¯2}-{112¯1} double twinning mechanisms in pure titanium. (January 2023) - Zhang, Hao; Ou, Xiaoqin; Ni, Song; Yan, Hongge; Liao, Xiaozhou; Song, Min
Highlights: The { 11 2 ¯ 1 } twin embryo is composed of a group of pyramidal stacking faults (PSFs) with 6 d { 11 2 ¯ 1 } or 8 d { 11 2 ¯ 1 } caused by successive slip of partial dislocations with the Burgers vector of 1 36 < 11 2 ¯ 6 ¯ > M . The growth of { 11 2 ¯ 1 } twin can be carried out by the slip of twinning dislocations (TDs) b ⇀ 1  =  1 6 ( 4 γ 2 + 1 ) < 1 ¯ 1 ¯ 26 > ± 1 2 < 1 1 ¯ 00 >. The interfacial structures of { 11 2 ¯ 1 } twins have the terraced character with short coherent ( 11 2 ¯ 2 )||( 11 2 ¯ 0 ) facets and coherent TB segments, and (0001)||( 11 2 ¯ 4 ) facets. The { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twin structure can form through the dissociation of the TD b ⇀ 1 ( 11 2 ¯ 2 ) at the { 11 2 ¯ 2 } twin tip or by the interaction between a basal < a > dislocation and a { 11 2 ¯ 2 } twin boundary (TB). The coherent twin interfaces can form at their intersected interfaces after formation of { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twin structure. Abstract: The { 11 2 ¯ 1 } twinning and { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twinning mechanisms in pure Ti are systematically investigated using molecular dynamics (MD) simulations. MD simulation results indicate that a { 11 2 ¯ 1 } twin embryo is composed of a group of pyramidal stacking faults (PSFs) with 6 d { 11 2 ¯ 1 } or 8 d { 11 2 ¯ 1 }, caused by the successive slip of partial dislocations with the Burgers vector of 1 36 〈 11 2 ¯ 6 ¯ 〉 M . The migration of { 11 2 ¯ 1 } twin boundaries (TBs) is mainly carried out by the slip of twinning dislocations (TDs) b ⇀ 1  =  1 6 ( 4 γ 2 + 1 ) < 1 ¯ 1 ¯ 26 > ± 1 2 < 1 1 ¯ 00 >. Two { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twinning mechanisms are discovered. One is that a { 11 2 ¯ 1 } twin forms and grows at the { 11 2 ¯ 2 } twin tip through the dissociation of the TD b ⇀ 1 ( 11 2 ¯ 2 ) at the { 11 2 ¯ 2 } twin tip, forming the { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twin structure. The other is that a basal < a >T dislocation interacts with a { 11 2 ¯ 2 } TB, forming a twin embryo composing of a group of PSF with the 6 d { 11 2 ¯ 1 ¯ } and leaving a step at the { 11 2 ¯ 2 } TB, eventually forming the { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twin structure. The interfacial structures of { 11 2 ¯ 1 } twins have the terraced character with short coherent ( 11 2 ¯ 2 )||( 11 2 ¯ 0 ) facets and coherent twin boundary (CTB) segments. In addition, (0001)||( 11 2 ¯ 4 ) facets with a disclination dipoles feature can form at twin tips. The coherent twin interfaces form at their intersected interfaces during the { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twinning process. Our present findings may provide clues for designing Ti alloys with excellent strength–ductility properties through obtaining a high-volume fraction of coherent interfaces in terms of { 11 2 ¯ 2 }-{ 11 2 ¯ 1 } double twins. Graphical abstract: Image, graphical abstract